Passivation-layer thickness and field-plate optimization to obtain high breakdown voltage in AlGaN/GaN HEMTs with short gate-to-drain distance. (June 2021) - Iwamoto, Takuma; Akiyama, Seiya; Horio, Kazushige
Abstract: A two-dimensional analysis of the off-state breakdown characteristics in field-plate AlGaN/GaN HEMTs is performed. The gate-to-drain distance is 1.5 μm, and the parameters are the SiN passivation-layer thickness d and the field-plate length L FP . For a moderate d of 0.1 μm, the breakdown voltage V br increases with L FP, and takes an maximum value ( 400 V) around L FP = 0.3 μm, and decreases when L FP becomes even longer. This decrease is attributed to the fact that the drain voltage is almost applied along the region between the field plate and the drain. For thin d ≤ 0.03 μm, V br becomes relatively low (≤150 V) when L FP becomes long (≥ 0.6 μm). This is attributed to the fact that when d is very thin, the field plate acts like a gate electrode. When d is relatively thick (≥0.3 μm), V br decreases at L FP = 0.3 μm as compared to the case of d = 0.1 μm, and it decreases to 250 V at d = 0.5 μm. This is because the field-plate effects become weak for thick d . The optimum thickness of the SiN passivation layer is approximately 0.1–0.2 μm and V br peaks at approximately 400 V when L FP = 0.3 μm. The novelty of this paper is to show the dependence of V br on the passivation-layer thickness d and the field-plate length L FP when the gate-drain distance is short. Highlights: 2D analysis of field-plate AlGaN/GaN HEMTs with short gate-to-drain distance is performed. Dependence of breakdown voltage on passivation-layer thickness d and field-plate length LFP is analyzed. Optimum values of d and LFP are obtained to achieve high breakdown voltage.